Undetected non-conformities in material processing led to a service failure in a casing hanger during pre-fracture operation. (October 2019) - Cirimello, Pablo; Otegui, Jose Luis; Aguirre, Alberto; Carfi, Guillermo
Abstract: The failure of a 5″ casing hanger at an oil well led to costly workover operations and lost production. The brittle failure was due to the instantaneous propagation of a circumferential fracture, initiated at a geometrical stress raiser. Combined operation stresses from internal pressure, casing weight and tightening torque were close to the yield strength of the material. If the material had sufficient ductility, plastic deformation would have led to stress relaxation and redistribution. But a SAE/AISI 4140 steel with a low forging ratio, plus a poor heat treatment and incomplete quenching, led to a banded microstructure with both low strength and toughness, and a consequent limited capacity for plastic deformation. Geometric discontinuities due to elongated inclusions and other microestructural defects justify crack propagation at the reported service loads. Quality assurance failed to prevent unacceptable pieces. Some recommendations are provided to reduce the likelihood of recurrence in new hangers: an appropriate microstructure must be assured, controlling the forging stages and heat treatment parameters. The representativeness of test coupons used for quality control must be ensured. Re -evaluating the geometry of the casing hanger and switching to a steel with higher hardenability would lead to more defect - tolerant components. Highlights: The failure of a 5" casing hanger at an oil well led to costly workover operations and lost production. The brittle failure was due to the instantaneous propagation of a circumferential fracture, initiated at a geometrical stress raiser. Geometric discontinuities due to elongated inclusions and other microstructural defects justify crack propagation at the reported service loads. Quality assurance failed to prevent unacceptable pieces.